Sphingolipid Metabolism and Signaling in Lung Cancer: A Potential Therapeutic Target. (28th June 2022) - Lin, Mengmeng; Li, Yingying; Wang, Shiyuan; Cao, Bo; Li, Chunyu; Li, Guohui
Abstract : Sphingolipids are important bioactive lipids that not only play an important role in maintaining the barrier function and fluidity of cell membranes but also regulate multiple processes in cancer development by controlling multiple signaling pathways in the signal transduction network. Dysregulation of sphingolipid metabolism is thought to be one of the most important dysregulated pathways in lung cancer, the most prevalent type of cancer in terms of incidence and mortality worldwide. This article focuses on lung cancer, reviewing the important lipids in sphingolipid metabolism and the related enzymes in relation to lung cancer progression and their effects on the tumor microenvironment and discussing their roles in the diagnosis and treatment of lung cancer.